“To understand the kidney is to understand life — from cell to society.” - authors, No (KIDNEYS, 2025)
Dear colleagues, readers, and friends, You are holding the fourth issue of Kidneys, a journal that continues our shared mission: to unite knowledge, experience, and humanity around one of the most delicate systems in the human body. The kidney is not just an organ. It is a source.